2015
DOI: 10.1186/1944-3277-10-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence and description of the mosquitocidal and heavy metal tolerant strain Lysinibacillus sphaericus CBAM5

Abstract: Lysinibacillus sphaericus CBAM5, was isolated from subsurface soil of oil well explorations in the Easter Planes of Colombia. This strain has potential in bioremediation of heavy-metal polluted environments and biological control of Culex quinquefasciatus. According to the phylogenetic analysis of 16S rRNA gene sequences, the strain CBAM5 was assigned to the Lysinibacillus sphaericus taxonomic group 1 that comprises mosquito pathogenic strains. After a combination assembly-integration, alignment and gap-fillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 55 publications
0
24
0
1
Order By: Relevance
“…In addition, according to OT4b.31, CBAM5, and III(3)7 strain genomes, there were annotated genes involved in the denitrification processes [8][9][10] such as nitric oxide and nitrous oxide reduction to molecular nitrogen. In addition, according to OT4b.31, CBAM5, and III(3)7 strain genomes, there were annotated genes involved in the denitrification processes [8][9][10] such as nitric oxide and nitrous oxide reduction to molecular nitrogen.…”
Section: Sphaericus Nitrogen Fixer and Nitrifying Bacteriamentioning
confidence: 99%
“…In addition, according to OT4b.31, CBAM5, and III(3)7 strain genomes, there were annotated genes involved in the denitrification processes [8][9][10] such as nitric oxide and nitrous oxide reduction to molecular nitrogen. In addition, according to OT4b.31, CBAM5, and III(3)7 strain genomes, there were annotated genes involved in the denitrification processes [8][9][10] such as nitric oxide and nitrous oxide reduction to molecular nitrogen.…”
Section: Sphaericus Nitrogen Fixer and Nitrifying Bacteriamentioning
confidence: 99%
“…sphaericus CBAM5 is responsible for the great efficiency as these living bacteria present active and passive mechanisms for gold removal, such as absorption and adsorption, respectively [14]. In the case of adsorption, it has previously been shown that this bacterium presents an S-Layer protein that assembles in the cell wall and acts as an ion trap [18]. Moreover, it is known that this protein possesses functional groups with affinity to metals like Au(III) and thus, complexation may occur after the exposure of L. sphaericus CBAM5 to that metal ion.…”
Section: Discussionmentioning
confidence: 99%
“…The strain L. sphaericus CBAM5 has shown a great potential to capture several metal ions like gold and mercury [15][16][17]. A study of its genomic sequence has shown that it possesses several coding regions for S-Layer proteins and it presents heavy metal efflux pumps that help the cell to resist high concentrations of metal ions [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…The recent sequencing of L. sphaericus Ot4b31 genome (Peña‐Montenegro & Dussán, ) and resequencing of L. sphaericus CBAM5 genome (Peña‐Montenegro et al., ) and KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis identified proteins that might participate in peripheral pathways for degradation of benzoate, amino benzoate, toluene, and other aromatic compounds, which might be an indication of the ability of this genera to biodegrade TPH.…”
Section: Introductionmentioning
confidence: 99%